Intrapersonal communication about the meaning of early marriage in Bandung City - Ilham, Yanuar; Surahman, Irmawati; Reza, Faisal; Sugiarta, Nugraha; Lestari, Anggita (Jurnal Kajian Komunikasi, 2023)
Background: Early marriage is a prevalent practice in Cigondewah Rahayu Village, Bandung City. From a psychological and social perspective, early marriage can lead to emotional immaturity and underdeveloped cognitive abilities among young brides. The persistence of traditional customs surrounding early marriage in the area serves as a compelling motivation for researchers to investigate this phenomenon. Purpose: This study aims to explore the community’s interpretation of early marriage from the perspective of intrapersonal communication. Additionally, it seeks to understand the experiences of individuals who have participated in early marriages in Cigondewah Rahayu Village, Bandung City. Methods: This research employs a qualitative approach, drawing on Alfred Schutz’s phenomenological studies and the theory of Symbolic interactionism. Informants were selected using a purposive sampling technique. Data analysis involved techniques such as data reduction, presentation, and verification. Results: The findings indicate that, within the context of intrapersonal communication, early marriage is commonly perceived as a normal practice within the local community, deeply rooted in historical traditions. Participants view early marriage as a ritual that holds religious significance. Moreover, they believe that it facilitates the development of a mature mindset, fostering independence and generating positive impacts in various aspects of their lives, particularly within their social interactions. Implications: Based on the study’s findings, it is important to raise public awareness regarding the potential risks associated with early marriage. Given the unstable mental condition of young individuals, engaging in early marriage can give rise to challenges within the household, as their psychological development is not yet fully equipped to handle the responsibilities and complexities of married life.